A Brief Introduction on Prof. Rong’s Mathematical Work (Journal of Mathematical Study, 2025)
Xiaochun Rong was born on June 17th, 1954. He graduated from Beijing NormalCollege (now Capital Normal University) in 1982, and received his Ph.D. from StonyBrook University in 1990. Rong was a Sloan Research Fellow in 1996-1998, and an NSFresearch grant awardee in 1994-2013. He has been a distinguished professor at RutgersUniversity in New Brunswick since 2008. Rong was a 2002 ICM invited speaker, and a2017 Fellow of the American Mathematical Society.